Analysis of The Implementation of The Double Track Program in Improving Entrepreneurial Interests of Grade XI Students at SMAN 1 Berbek (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: This study aims to test the influence of the Double Track Culinary Arts and Double Track Make-up Programs on increasing the interest in entrepreneurship of class XI students at SMAN 1 Berbek.Method: This study's population consisted of 60 Double-Track participants. The saturated sampling technique was used for sampling. The data collection methods used were observation and questionnaires, and the data analysis technique used was multiple linear regression.Research Finding: The study's results show that the Double Track Culinary Arts and Double Track Make-up Arts variables have a positive effect on increasing the interest in entrepreneurship of class XI students at SMAN 1 Berbek.Originality: This research provides a more detailed picture of the Double Track program's influence on increasing students' interest in entrepreneurship.